2020
DOI: 10.21726/abc.v7i3.141
|View full text |Cite
|
Sign up to set email alerts
|

Posição e profundidade de semeadura na formação de mudas de Peltophorum dubium (Sprengel) Taubert (Fabaceae)

Abstract: A canafístula [Peltophorum dubium (Sprengel) Taubert (Fabaceae)] é uma espécie nativa promissora para a produção de madeira. Assim, para a formação das mudas, a profundidade das sementes e a sua posição de deposição na semeadura são alguns dos vários fatores que exercem influência no seu crescimento e desenvolvimento. O objetivo do presente trabalho foi avaliar a produção de mudas de canafístula, em função da posição da semente no substrato e da profundidade de semeadura. O experimento foi conduzido em casa de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The authors concluded that sowing depth did not interfere with plant height. Acacia polyphylla DC seeds, planted at 1.4 and 2.8 cm deep, and Peltophorum dubium (Sprengel) Taubert seeds, planted at 1 and 3 cm deep, showed the best results for emergence rate (Rodrigues et al, 2016;Zuffo et al, 2020).…”
Section: Initial Growthmentioning
confidence: 99%
“…The authors concluded that sowing depth did not interfere with plant height. Acacia polyphylla DC seeds, planted at 1.4 and 2.8 cm deep, and Peltophorum dubium (Sprengel) Taubert seeds, planted at 1 and 3 cm deep, showed the best results for emergence rate (Rodrigues et al, 2016;Zuffo et al, 2020).…”
Section: Initial Growthmentioning
confidence: 99%